2007
DOI: 10.1177/0961203307080636
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive clinical features of pediatric systemic lupus erythematosus in three different age classes

Abstract: It is estimated that around 20% of patients with systemic lupus erythematosus (SLE) have their onset in childhood but there have been conflicting data about the prevalence and severity of the clinical features in different age classes. We conducted this study to analyse the clinical features of patients with pediatric SLE (pSLE) with onset in infancy, prepubertal and postpubertal age. The charts of patients followed at the Department of Pediatrics, University of Padua, who met the criteria for SLE diagnosis, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
78
7
12

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(111 citation statements)
references
References 26 publications
11
78
7
12
Order By: Relevance
“…All rights reserved. with < 2 years had a median disease duration of 14 months (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Arthritis Care and Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…All rights reserved. with < 2 years had a median disease duration of 14 months (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Arthritis Care and Researchmentioning
confidence: 99%
“…Previous retrospective studies suggested that age at disease onset (10)(11)(12)(13) and age at diagnosis (9) may influence disease expression in terms of initial clinical presentation, pattern of organ involvement and serological findings. The small sample size of these studies performed in North America, Europe and Asian cSLE populations (8)(9)(10)(11)(12)(13) precludes a definitive conclusion about their findings, particularly regarding the early-onset cSLE patients (<6 years).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Children present with more acute illness and have more frequent renal, hematologic and central nervous system involvement at the time of diagnosis compared to adults with SLE. When comparing pre-pubertal to post-pubertal onset of pediatric SLE, the former group presents more often with hemolytic anemia and renal involvement whereas in the latter group cutaneous and musculoskeletal features are more common at disease onset [2]. Haematological abnormalities (anemia, autoimmune hemolysis, aplastic anemia, leukopenia, and thrombocytopenia) are frequently encountered in patients with SLE and are a part of the American Rheumatic Association criteria for classifying the disease.…”
Section: Introductionmentioning
confidence: 99%